WEBTOON KERAJAAN INSTRUMEN ENKULTURASI - Aryanti, Alisha; Dwiatmini, Sriati; Setyobudi, Imam (Institute of Indonesia Arts and Culture (ISBI) Bandung, 2025)
Abstrak: Permasalahan penelitian ini ialah bagaimana nilai-nilai etika hidup dalam webtoon tema kerajaan dapat memunculkan fungsi enkulturasi bagi pembacanya. Tujuan penelitian adalah menjelaskan webtoon tema kerajaan dapat menjadi media enkulturasi bagi pembacanya. Menggunakan metode penelitian kualitatif dengan teknik pengumpulan data berupa observasi partisipatif, wawancara, dokumentasi, serta studi pustaka. Menggunakan teori fungsionalisme Bronislaw Malinowski untuk menganalisis fungsi dari webtoon. Hasil penelitian menunjukkan bahwa webtoon memiliki fungsi tambahan yakni sebagai media enkulturasi. Kata Kunci: Webtoon, fungsi, enkulturasi, nilai-nilai etika hidup Abstract: The problem of this research is how the ethical values of life in the royal theme webtoon can bring out the enculturation function for the readers. The purpose of this research is to explain that royal theme webtoon can be a medium of enculturation for its readers. Using qualitative research methods with data collection techniques in the form of participatory observation, interviews, documentation, and literature study. Using the functionalism theory of Bronislaw Malinowski to analyze the function of the webtoon. The results showed that the webtoon has an additional function, namely as an enculturation medium. Keywords: webtoon, function, enculturation, ethical values of life